Real-world data analysis of adjuvant capecitabine for triple-negative breast cancer after neoadjuvant chemotherapy - Godoy-Ortíz, Ana; Lendínez-Sánchez, Gonzalo; Zalabardo, Manuel; Pascual, Javier; López-Pascual, Ana; Cantero, Alexandra; Ribelles, Nuria; Iglesias, Marcos; Villar, Ester; Pajares, Bella; Díaz-Redondo, Tamara; Domínguez-Recio, Maria Emilia; et al. (Frontiers in Oncology, 2025)
PurposeEvaluate real-world outcomes in three cohorts of patients with early-stage triple-negative breast cancer (TNBC) treated with neoadjuvant chemotherapy (NAC): (1) patients who achieved pathological complete response (pCR); (2) patients without pCR who didn’t receive adjuvant chemotherapy; and (3) patients without pCR who received adjuvant capecitabine.MethodsRetrospective cross-sectional study from two hospitals in Málaga. Patients with TNBC received standard NAC followed by surgery. Between 2004 and 2015, patients not achieving pCR received no further systemic therapy. From 2015 onward, these patients were treated with adjuvant capecitabine. Kaplan–Meier and log-rank tests were used to compare disease-free survival (DFS) and overall survival (OS).ResultsA total of 312 patients were included in the study. 133 achieved pCR, 84 patients didn’t achieve pCR and didn’t receive adjuvant capecitabine and 95 patients didn’t reach pCR and received adjuvant capecitabine. 89 patients experienced recurrence and 70 patients died. Patients who achieved pCR had a significantly higher DFS (HR 0.21 CI95% 0.12-0.36, p<0.0001) and higher overall survival (HR 0.27 CI95% 0.15-0.49, p<0.0001) compared to those who didn’t. Statistically significant differences in DFS and OS were observed among the three cohorts (DFS: p<0.00001; OS: p=0.00005). However, no statistically significant differences were found between cohorts 2 and 3 in terms of DFS (p=0.94) or OS (p=0.34).ConclusionsPatients who achieved pCR had better outcomes compared to those who didn’t. Among patients who didn’t achieve pCR, the addition of capecitabine didn’t result in significant improvements in DFS or OS compared to those who didn’t receive adjuvant treatment.